Wybrane teorie leżące u podstaw współczesnego paradygmatu wojny - Mazur-Bubak, Monika (Hybris, 2015)
This article will try to indicate the most important theories which constitute the modern paradigm of the war. The theory of the war is an important issue in political philosophy because it accentuates how the boundaries of the existence and the functioning of the state are drawn. Seeking works that form the basis of the paradigm, one should begin with presenting a specific structure of the theory proposed by T. Kuhn. On this basis the article will be divided into three parts. The first part is focused on the construction of Kuhn’s scientific paradigm. Additionally in order to prove the meaningful use of paradigmatic structure in issues connected to humanities and philosophy Giorgio Agamben thesis will also be presented. The next part will expose the main elements of Carl von Clausewitz's theory of war. The most important of these is an assumption that war is the continuation of political action that seeks to compel the enemy to fulfill “our will”. The second element to be tested will be a political concept of Carl Schmitt along with its specific categories of the enemy and the friend. The second element to be tested will be Carl Schmitt’s the Concept of the political with its specific categories: the enemy and the friend. The third part of the paper will present the concept of Jerzy Wiatr. Its task will be to supplement the paradigm by showing that the parties of the war may be a “political community” and not only the state. This will help to extend the applicability of the paradigm in various fields of the social sciences. The ultimate aim will be to convince the reader that these theories are the most important part of the paradigm. Moreover, there is a high probability that they became the basis for the modern paradigm of the war.